2020
DOI: 10.1001/jama.2020.15580
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for SARS-CoV-2 in Breast Milk From 18 Infected Women

Abstract: Concern has been raised that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may be transmitted to infants by breastfeeding. A number of organizations advise that women infected with SARS-CoV-2 may choose to breastfeed with protections to prevent transmission of the virus through respiratory droplets. Of 24 case reports on breast milk samples from women infected with SARS-CoV-2, viral RNA was detected in 10 samples from 4 women. 1-6 In some cases, environmental contamination or retrograde flow fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
249
0
13

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(270 citation statements)
references
References 6 publications
8
249
0
13
Order By: Relevance
“…explored the efficiency of holder pasteurization against SARS-CoV-2 in 5 milk samples and found that infectivity of all 5 tested SARS-CoV-2 isolates is completely eliminated by this treatment. This confirms studies where holder pasteurization of milk spiked with three early SARS-CoV-2 isolates prevented viral infection of monkey derived Vero cells[7][8][9] . We verify the efficiency of holder pasteurization upon inclusion of additional viral strains, encompassing the dominant pandemic variant D614G that shows increased fitness in cell culture (Netherlands/01, UKEssen) 10 as well as highly susceptible human Caco-2 cells that express the viral entry factor transmembrane serine protease 2 (TMPRSS2).…”
supporting
confidence: 85%
“…explored the efficiency of holder pasteurization against SARS-CoV-2 in 5 milk samples and found that infectivity of all 5 tested SARS-CoV-2 isolates is completely eliminated by this treatment. This confirms studies where holder pasteurization of milk spiked with three early SARS-CoV-2 isolates prevented viral infection of monkey derived Vero cells[7][8][9] . We verify the efficiency of holder pasteurization upon inclusion of additional viral strains, encompassing the dominant pandemic variant D614G that shows increased fitness in cell culture (Netherlands/01, UKEssen) 10 as well as highly susceptible human Caco-2 cells that express the viral entry factor transmembrane serine protease 2 (TMPRSS2).…”
supporting
confidence: 85%
“…In one of the cases, SARS-CoV-2 RNA was detected in milk at days 10, 12, and 13, coinciding with SARS-CoV-2 positive diagnostic testing of the newborn, who developed mild COVID-19 symptoms from day 10 on. However, as described by Chambers et al detection of viral RNA by reverse transcriptasepolymerase chain reaction (RT-PCR) does not equate with infectivity (19). Overall, these data highlight the importance of prevention and early detection and follow-up in neonates, in whom management and treatment still need to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…As of August 26, 2020, there had been over 24 million confirmed cases, and more than 800,000 deaths due to the disease (2). The risk of death due to coronavirus disease 2019 (COVID- 19) increases exponentially with age. Thus, mortality rates are in the order of 0.12% in children, but as high as 14.8% in older individuals (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…62,63 It is unclear what the impact of freezing and thawing on infectivity would be. However, Walker and colleagues 64 provide evidence that Holder pasteurization (but not cold storage) inactivates SARS-COV2; Unger et al 65 and Chambers et al 66 have also shown that Holder pasteurization inactivates SARS-CoV-2 and the former that holding milk at room temperature for 30 minutes also reduces infectious viral titers.…”
Section: Frameworkmentioning
confidence: 99%